Uma reflexão sobre o uso de tirinhas no livro didático: Da leitura escolar à leitura da vida - Lima, Bruna Mara Rosin de (2020)
This study is affiliated with the French Discourse Analysis theory and problematizes the presence of comic strips in the collection of Portuguese and Language textbooks – 7th grade (CEREJA and MAGALHÃES, 2015). The problem issue of the study was caused by the erasure of gender discourse since when bringing the comic strips, the research shows that the textbook favors reading as a pretext for solving exercises on the use of language elements through a purely grammatical approach. In the course of the study, moments were organized in order to reflect and problematize the presence of comic strips by the material. In this process, it was considered, yet, the voice of official speeches that cross and constitute school pedagogical practices. In the analyzes made, we sought to show the limitations in referrals to the genre through the textbook and, following, we presented a reading work that causes the questioning of the discourse in the selected corpus, while we point to the perspective of a reading work through the discursive look, it is, taking into account the socio-ideological aspects as constitutive of the meanings printed in the textual materiality. With this organized analytical movement, the study went on to apply the pedagogical proposal, which occurred in a State School in the City of Dois Vizinhos/Paraná, in a 7th grade class. As a result of the work, we understand the need for studies that mainly involve reading and reflection, which enable the teacher to work in a discursive perspective in the face of didactic material and the teaching of reading and, therefore, of the teaching of the Portuguese language. Thus, distancing itself from the limitations of mere decoding and other reductionist and silencing practices still present in the school universe that use gender only as a pretext for grammatical teaching, in the absence of discussions about the meaning effects present in the discursive materiality.